2002
DOI: 10.1021/om020133o
|View full text |Cite
|
Sign up to set email alerts
|

Stable η1-Alkynyl−μ,η12-Alkenyl Complexes from the Reaction of Terminal Alkynes with Encumbered Dinuclear Platinum Compounds and Their Formyl, Methoxycarbonyl, and Hydride Derivatives

Abstract: The stepwise reaction of terminal alkynes with [(OC)Pt(μ-PBut 2)2Pt(H)(PBut 2H)]OTf yields intermediate η1-alkynyl−hydride-bridged complexes, and then stable η1-alkynyl/alkenyl-bridged derivatives containing an electrophilic carbonyl ligand. The latter is attacked by nucleophiles (H- and MeO-) to give a rare platinum formyl species, which is slowly converted into a stable hydride or a stable methoxycarbonyl complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 40 publications
2
5
0
Order By: Relevance
“…As far as we know, this structural feature has no precedent in the literature, the most similar examples being a (μ-hydroxy)(μ-alkyne) bridging system in a pentanuclear ruthenium cluster and a (μ-hydroxy)(μ-allenylidene) trinuclear osmium cluster . Notwithstanding, a good number of vinyl groups acting as bridging ligands between two transition metals have been reported, although the examples containing platinum are really scarce, in particular, those referring to homopolynuclear derivatives. ,, It should be noted that recently a (μ-hydride)(μ-vinyl) dinuclear intermediate species has been proposed in the formation of the (μ-alkylidene) complex [Pt 2 (dppm) 2 (μ-H)(μ-CHCH 2 Ph)](BF 4 ) 5 ORTEP view of [ cis,cis -(PPh 3 ) 2 Pt{μ-1κ C α :η 2 -CHCHC(OH)Ph 2 }(μ-OH)Pt(C 6 F 5 ) 2 ] ( 5f ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as we know, this structural feature has no precedent in the literature, the most similar examples being a (μ-hydroxy)(μ-alkyne) bridging system in a pentanuclear ruthenium cluster and a (μ-hydroxy)(μ-allenylidene) trinuclear osmium cluster . Notwithstanding, a good number of vinyl groups acting as bridging ligands between two transition metals have been reported, although the examples containing platinum are really scarce, in particular, those referring to homopolynuclear derivatives. ,, It should be noted that recently a (μ-hydride)(μ-vinyl) dinuclear intermediate species has been proposed in the formation of the (μ-alkylidene) complex [Pt 2 (dppm) 2 (μ-H)(μ-CHCH 2 Ph)](BF 4 ) 5 ORTEP view of [ cis,cis -(PPh 3 ) 2 Pt{μ-1κ C α :η 2 -CHCHC(OH)Ph 2 }(μ-OH)Pt(C 6 F 5 ) 2 ] ( 5f ).…”
Section: Resultsmentioning
confidence: 99%
“…The use of transition metal complexes to activate carbon−hydrogen bonds has become one of the most pursued goals of organometallic chemistry. Nowadays, the activation of C−H bonds in alkynes is one of the most active fields of research in this area, mainly due to their implications in the alkyne/vinylidene tautomerization, as well as in some catalytic processes. In this context, we have recently reported that [ cis -Pt(C 6 F 5 ) 2 (thf) 2 ] reacts with the alkyne platinum(0) derivative [Pt(η 2 -HC⋮CPh)(PPh 3 ) 2 ] to yield, through an unexpectedly easy C−H activation, the (μ-hydride)(μ-alkynyl) diplatinum complex [ cis , cis -(PPh 3 ) 2 Pt(μ-H)(μ-1κ C α :η 2 -C⋮CPh)Pt(C 6 F 5 ) 2 ], while the reaction of the same solvate substrate [ cis -Pt(C 6 F 5 ) 2 (thf) 2 ] with the hydride−alkynyl platinum(II) complex [ trans -PtH(C⋮CPh)(PPh 3 ) 2 ] leads, also under very mild reaction conditions, to the (μ-hydride)(μ-alkynyl) diplatinum isomer [ trans -(PPh 3 )(C 6 F 5 )Pt(μ-H)(μ-1κ C α :η 2 -C⋮CPh)Pt(C 6 F 5 )(PPh 3 )]. , Although many different structural types of dimeric hydride-bridged platinum complexes have been reported, these two acetylide-bridged diplatinum isomers belong to a rare class of these compounds, which contains mixed bridging systems consisting of a hydride and a hydrocarbon ligand. In fact, as far as we are aware, the only other reported examples are the analogous cationic (μ-alkylidene)(μ-hydride) complexes [Pt 2 (L−L) 2 (μ-CHCH 2 Ar)(μ-H)] + and the cationic (μ-hydride)(μ-carbonyl) or (μ-hydride)(μ-isocyanide) derivatives [Pt 2 (L−L) 2 (μ-CX)(μ-H)] + (X = O , or NR 33 ), which are formally diplatinum(I) species.…”
Section: Introductionmentioning
confidence: 99%
“…Complex [(C 6 F 5 ) 2 Pt(μ‐PPh 2 )(μ‐H)Pt(PHPh 2 )(PPh 3 )] (Pt–Pt) ( 63 ) is obtained from reactions of cis ‐[Pt(C 6 F 5 ) 2 (PHPh 2 ) 2 ] with [Pt(norbornene) 3 ] and PPh 3 45. The alkynyl complex [(PH t Bu 2 )(PhC 2 )Pt(μ‐P t Bu 2 )(μ‐H)Pt(PH t Bu 2 )(CO)] + (Pt–Pt) ( 64 ) is produced by the reaction of 53b with phenylacetylene 60. Bridging hydrides resulting from protonation of the Pt I –Pt I bond are obtained upon treatment of 53a with triflic acid {complex [(PH t Bu 2 )(CO)Pt(μ‐P t Bu 2 )(μ‐H)Pt(PH t Bu 2 )] 2+ (Pt–Pt) ( 65 )}51 or by action of 2 equiv.…”
Section: Phosphanido‐bridged Dinuclear Platinum Complexesmentioning
confidence: 99%
“…[1][2][3][4][5][6] Of particular importance is the C-H bond activation of terminal alkynes due to their involvement in alkyne/vinylidene tautomerization, as well as in some catalytic processes. [7][8][9][10][11][12][13][14][15][16] In this field, our group has recently reported an easy C-H bond activation of a terminal alkyne at platinum(0) derivatives [Pt(g 2 -HC≡CR)(PPh 3 ) 2 ], (R = Ph, (4-CH 3 )C 6 H 4 , (4-CN)C 6 H 4 , CMe=CH 2 , C(OH)Me 2 and C(OH)-EtMe), in very mild conditions, by reaction with the platinum(II) species [cis-Pt(C 6 F 5 ) 2 (thf) 2 ], to yield the (l-hydride)(l-acetylide) diplatinum complexes [cis,cis-(PPh 3 ) 2 Pt(l-H)(l-1jC a :g 2 -C≡CR)-Pt(C 6 F 5 ) 2 ] (Chart 1, i). 17, 18 Interestingly, the reaction, in very mild conditions, of the same solvate [cis-Pt(C 6 F 5 ) 2 (thf) 2 ] with the isomeric Pt(II) substrates [trans-PtH(C≡CR)(PPh 3 ) 2 ], leads to the corresponding (l-hydride)(l-acetylide) diplatinum isomers [trans-(PPh 3 )(C 6 F 5 )Pt(l-H)(l-1jC a :g 2 -C≡CR)Pt(C 6 F 5 )(PPh 3 )] (Chart 1, ii).…”
Section: Introductionmentioning
confidence: 99%